Xanthoma disseminatum - Sharma, Deepak; Garg, Nikha; Singh, Tarunveer; Dhillon, Kanwarjit S.; Tandon, Nishi; Umar, Mohd Sadiq; Agrawal, Vidhi; Srivastava, Ritika (International Journal of Advances in Medicine, 2017)
Xanthoma disseminatum is a rare, benign, normolipemic form of non-Langerhans cell histiocytosis affecting the skin and mucous membranes. The cutaneous manifestations consist of hundreds of papules that are red – brown at first and then become yellowish. The papules symmetrically involve the eyelids, trunk, face and proximal extremities and in flexures and folds, tend quickly to merge, forming soft plaques. It is frequently associated with diabetes insipidus. Biopsy specimens show a mixture of histiocytes, foam cells, and inflammatory cells. Later, foam cells predominate and Touton giant cells are frequently present. This chronic disease has no known established treatment.